Women's political participation in the United States after women's suffrage: women's representation in the legislature of the house of representatives and the senate - Silalahi, Ezra Sherly Margareth (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2024)
Historically, women have confronted formidable barriers to political participation, entrenched by patriarchal norms. Despite the ratification of the Nineteenth Amendment in the United States, which granted women voting rights, substantive representation remains elusive. This study investigates the persistent gender gap in political representation, focusing on the 113th congressional elections. Employing liberal feminist theory and democratic principles, it aims to elucidate the urgency of addressing women's underrepresentation in legislative bodies. Through literature review and quantitative analysis of electoral data, this research seeks to uncover the impact of electoral systems on women's political engagement. Results reveal stark contrasts between countries like the US and Rwanda, emphasizing the critical role of electoral mechanisms in fostering gender parity. By illuminating these disparities, this study underscores the imperative for policy interventions to ensure equitable political participation for women, thereby advancing democratic ideals and societal progress.